قواعد منهجيَّة للتفسير الاجتماعي وتطبيقاتها من تفسير المنار لسورة النساء = Methodological rules for social interpretation and its applications from Tafsīr al-Manār to Surah al-Nisā’ - Alaboosi, Abdullah; Ahmad, Nadzrah; Muhammad Ali, Nabilah (IIUM Press, International Islamic University Malaysia, 2018)
مما لا شك فيه أن تفسير المنار من أفضل التفاسير التي ألفت في التفسير الاجتماعي، وصياغة المعاني التي يهدف القرآن إليها في أسلوب شَي ق أخَّاذ، وتطبيق النص القرآني على ما في الكون من سنن الاجتماع، ونُظُم العمران؛ لذلك يهدف هذا البحث إلى استخراج مجموعة من العناصر والكلي ات التي ارتكز عليها منهج أصحاب تفسير المنار في تفسيرهم، لتجعل هذه الكليات المنهجي ة قواعد يسهل اتباعها ومعرفتها لكل من أراد أن يفهم أصول منهج تفسير المنار، أو أن يف سر القرآن اجتماعياً كما فعل رجال المدرسة الحديثة في التفسير. وقد اتبع الباحثون منهجين: الاستقرائي لجمع اآيات المتعلقة بالقواعد المنهجية، والتحليلي لدراسة محتوى تفسير المنار وتحليله بغية الوصول إلى النتائج المرجوة. ومن مقتضيات البحث أن تختار سورة النساء للقيام بهذه المهمة. وقد تم الخلوص إلى خمس قواعد عامة، منها: كشف الل بس والغُموض عن المصطلحات، والتوجيهات الشرعيَّة، وربطها بالمجتمع. ا ولاعتبار بتاريخ الأُمم والشعوب وربطُ الماضي بالحاضر. ومراعاةُ المُستجدَّاتِّ والتغريرات الحضاريَّة. وتتبرع مصالح الأحكام الشرعيَّة وتجليَة حِّكَمِّهَا، ا ولرجوع إلى سنن الفطرة ومقتضياتها. *********************************************************** There is no doubt that the interpretation of al-Qur'an (al-Manār) is one of the best social interpretation: through the formulation of meanings in the Qur'an in indeed a fascinating way, the application of the Qur'anic text on the universe, and the systems of urbanization. Therefore, this research aims at extracting a group of elements based on the interpretation of al-Manār. These methodologies are easily followed and known for anyone who wants to understand the origins of the Manārinterpretation method. The researcher has followed two main approaches: the inductive approach and the analytical method, by collecting the verses related to the methodological rules, and studying the content of the interpretation of al-Manārand analyzing it in order to achieve the desired results. For the purposes of the research, one surah was chosen, which is the Surah of al-Nisā’. Additionally, the analysis of the text of al-Manār’s interpretation of women's image and the pursuit of systematic rules, came to five general rules, such as the detection of ambiguity, the ambiguity of terms, legal directives and their link to society. Also, it considers the history of nations and peoples, linking the past to the present. and taking into account developments and changes in civilization.